A COMPARATIVE ANALYSIS OF ENGLISH TRANSLATIONS OF URDU SHORT STORIES IN THE PAKISTANI TEXTBOOKS AT BACHELORS AND INTERMEDIATE LEVELS - Faiza Arshad; Asma Naz (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study aimed to examine the lack of equivalence and to identify inadequacies in the English translations of the Urdu short stories in Pakistani Textbooks. Translation is one of the ways to communicate. However, the principal task in translation practice is to create the equivalence of the original text in the target text. This research also explored the semantic loss related to the cultural, political, religious, and social aspects of the source texts that occurred during the translation of the Urdu source texts into the English target texts. The study comprised of three Urdu short stories by Manto, Qasmi, and Abbas and their English translations selected from A Selection of Short Stories and One-Act Plays for Bachelor Students (2017) and Punjab Textbook 1 of English for Intermediate Students (2017). One English short story had been included in the Textbook for Bachelor students translated from the Urdu source text. Two English short stories had been included in the Punjab textbook translated from the Urdu source texts. This research was qualitative in nature and based on Hermeneutics as an interpretative framework for translation studies. Nida’s (1964) Formal and Dynamic Equivalence Theory served as a theoretical framework in this study. Different strategies, procedures and tools were used to analyze the process of translation. The present research used Vinay and Darbelnet’s (1995) Translation Tools for the analysis of the data. The method was selected to analyze and compare lexical, and syntactical similarities and differences between the source texts and target texts. The comparison revealed the lack of equivalence between the source texts and target text at a lexical and syntactical level.The analysis also revealed the semantic loss in the English translations of the three Urdu short stories.